“Nothing is ever easy”: Parent Perceptions of Intensity in Their Gifted Adolescent Children - Guthrie, Kate (Qualitative report, 2019)
Due to asynchronous development, gifted children often experience the world differently than their same-aged peers. Some experience unique intensities, or overexcitabilities, that render modifications in teaching and parenting. These intensities typically take on characteristics of emotional, intellectual, imagination, psychomotor, or sensual overexcitability. In this in-depth interview study, I explored parent perceptions of intensity in their gifted adolescent children. Three mothers participated and completed the Overexcitability Inventory for Parents-Two (OIP-II) prior to each interview. The parent responses to the OIP-II served as an elicitation device to begin our conversations. Thematic analysis revealed three main themes among the participants’ perceptions: (1) challenging behaviors of intense gifted children, (2) consequences of intensity, and (3) a parent’s search for understanding. These findings inform the understanding of intensity and overexcitability from parents’ points of view and provide insight into how intense gifted children behave outside of the classroom. I conclude the article with questions to consider regarding how to better support parents of young gifted children.